Proceedings of the 8th International Conference on Human-Agent Interaction 2020
DOI: 10.1145/3406499.3415079
|View full text |Cite
|
Sign up to set email alerts
|

A Socially-Aware Conversational Recommender System for Personalized Recipe Recommendations

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…As in ( Burke, 2002 ; Pecune et al, 2020a ), Cora relies on a hybrid approach combining knowledge-based (KB) and collaborative filtering techniques (CF) for this experiment. The recommendation process has three steps.…”
Section: Experiments 2: Evaluating the Influence Of Cora’s Nudges And Explanationsmentioning
confidence: 99%
“…As in ( Burke, 2002 ; Pecune et al, 2020a ), Cora relies on a hybrid approach combining knowledge-based (KB) and collaborative filtering techniques (CF) for this experiment. The recommendation process has three steps.…”
Section: Experiments 2: Evaluating the Influence Of Cora’s Nudges And Explanationsmentioning
confidence: 99%
“…A multi-view method is proposed in Chen et al (2020b) for the explainable conversational recommendation. The work of Pecune et al (2020) builds a socially aware CR system engaging its users through a rapportbuilding dialogue to improve users' perception.…”
Section: Related Workmentioning
confidence: 99%
“…After years of development, there is a lot of work to show that recommendation techniques have been successfully applied to disease prediction, disease prevention, medical diagnosis, and so on [62], [65], [85], [112], [113], [143], [161], [166]. Moreover, recent work has indicated that health RS has developed from the applications of basic recommendation techniques to the algorithm improvement and model innovation [13], [19], [67], [122], [146]. Here, the applications of recommendation techniques in healthcare are mainly divided into the following topics:…”
Section: Applications Of Recommendation Techniques In Healthcarementioning
confidence: 99%